A Potent Antioxidant Endogenous Neurohormone Melatonin, Rescued MCAO by Attenuating Oxidative Stress-Associated Neuroinflammation - Ling, Li; Alattar, Abdullah; Tan, Zhen; Shah, Fawad Ali; Ali, Tahir; Alshaman, Reem; Koh, Phil Ok; Li, Shupeng (Frontiers in Pharmacology, 2020)
IIschemic stroke is an acute neurological syndrome either due to permanent or temporary obstruction of blood. Such obstruction immediately triggers abrupt pathological cascading processes, which collectively lead to neuronal cell death. Oxidative stress and neuroinflammation in ischemic stroke are critical regulating events that ultimately lead to neuronal death. Complicated interplay exists between the two processes which occur through several stages. Most often, oxidative stress precedes the inflammatory mechanisms and includes several interconnected cascades that underlie the ischemic stroke pathology. In continuation of the previously published data, here, we further ruled out the protective role of melatonin in focal cerebral ischemic injury model. Administration of 5mg/kg dose of melatonin 30 min prior to ischemia reduced brain infarction associated with sequentially rescued neuronal apoptosis. Furthermore, melatonin attenuated neuroinflammatory markers and reactive oxygen species (ROS), induced by ischemic stroke, via halting the key players of mitogen stress family (p38/JNK). Besides, melatonin modulated the endogenously produced antioxidant enzyme, thioredoxin (Trx) pathway. These broader therapeutic efficacies of melatonin suggest that melatonin could be further investigated for its diverse therapeutic actions with multiple targets in recovering, preventing and halting the detrimental outcomes of MCAO, such as elevated oxidative stress, neuroinflammation, and neurodegeneration.